HARD WORK AND SMART WORK. WHAT IS THE DIFFERENCE? - Matkarimova Shohista Habibullayevna; Akhmedov Akbarjon Elmurod o‘g‘li (Innovative Development in Educational Activities, 2023)
Nowadays, it is becoming difficult to meet a person who is not busy. Everyone has their own personal life and different responsibilities. So we have a lot of activities to do and little time, so we have to use some methods to get everything done. Currently, many people use the two main world-recognized methods of "smart work" and "hard work". The first method gives the meaning of smart work, that is, it means to perform activities with full understanding of the training you are doing. The second one gives a strong, multitasking meaning, and this technique is based on completing many activities in a short time. By understanding and applying these techniques, people approach activities based on the importance and urgency of their work.